Editorial for Special Issue “Antibiotic Combination Therapy: A Strategy to Overcome Bacterial Resistance” - Helal F. Hetta; Yasmin N. Ramadan; Israa M. S. Al-Kadmy (Biomedicines)
Multidrug-resistant (MDR) bacterial infections have emerged as a critical global health threat, challenging the efficacy of existing antibiotics and undermining advances in modern medicine [...]